Pengaruh Pelatihan, Lingkungan Kerja dan Kompensasi Terhadap Kinerja Pegawai: SLR - Saepudin Saepudin; Achmad Fauzi; Ami Pujiwati (Dinasti Review, 2023)
This research aims to analyze the influence of training, work environment and compensation on employee performance. The method used is systematic literature review (SLR). The results showed the RQ1 indicated time, skill, ability, participant, material, method, objective, trainers and training needs as dominant indicators in training. Lighting, coworker, superior, work facilities and communication as indicators of the work environment. Salary, incentive, wage, premium, treatment, insurance, benefit and work facilities as indicators of compensation. Effectiveness, efficiency, responsibility, ability, cooperation, accuracy, quality and quantity as indicators of employee performance. The RQ2 the dominant analysis tools are SPSS-17, SEM-PLS and Path analysis. The RQ3 the majority of papers examined show that training, the environment of work and compensation have positive and significant effect on employee performance. However, a number of research papers show that training has no effect on employee performance. Partially, the work environment has no effect on the training structure. Compensation has no effect on employee performance.